STUDI LITERATUR ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE (TTW) - Chandro Surya Bagus Lumban Tobing; Waminton Rajagukguk (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to determine students’ mathematical connection abilities with the think talk write cooperative learning model. The type of research used is research with a qualitative approach. Qualitative research uses descriptive or verbal data from people who have behaved. The method used is literature study. The type of data used is secondary data. Secondary data is data that already exists, so we just need to find and collect existing data. The secondary data source used in this research is the influence of the cooperative learning model of the think talk write type on students’ mathematical connection .From the search results, the researchers found 3 journals and 2 thesis relevant to the research topic. From the journal it was found that there was an influence of the think talk write cooperative learning model on students’ mathematical connection abilities.